Digital Media and Knowledge Production Within Social Movements: Insights From the Transition Movement in Italy. (November 2019) - Pavan, Elena; Felicetti, Andrea
In this article, we aim at contributing to ongoing discussions on the nexus between digital media and social movements. We investigate how activists problematize the inclusion of digital media within their courses of action and exploit these tools to produce and diffuse alternative knowledge on the issues on which they mobilize. We do so by studying Transition Italia (TI), the Italian hub of the transnational Transition movement struggling for resilience and sustainability. First, we reconstruct how activists problematized the adoption of digital media within TI's courses of action. Second, we explore how activists leveraged Facebook affordances to produce and diffuse alternative knowledge on TI as a collective actor, its visions and practices, its action networks, and the political alternatives it aims to achieve. Far from being passive adopters of digital media, activists considered critically the inclusion of digital media within TI's activities in light of three elements of import to the national activist community: the appropriateness of mainstream digital platforms to inform citizens, the perceived efficacy of digital tools, and the attempt to distinguish themselves from the global Transition Network. Moreover, we show that activists engaged in a "knowledge curation work" by sharing links and creating and spreading original contents.